COUNSELLORS’ COMPETENCE AS INDICES FOR COUNSELLEES ATTRACTION IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA (Journal of Guidance and Counselling Studies, 2020)
This study examined the Counsellors’ competence-attributes on counsellees attraction in Public Secondary Schools in Anambra State. One research questions and one null hypothesis guided the study. The study adopted descriptive survey research design. The population of the study was all public senior secondary schools in Anambra state. The sample comprised 650 senior secondary students (338 males and 312 females) selected through simple random sampling method. The instrument used for data collection was a structured questionnaire developed by the researcher titled “Counsellors Competence as Indices for Counsellees Attraction (CCICA).The reliability of the instrument was determined using Cronbach Alpha estimate and it yielded a co-efficient of 0.78. Mean and standard deviation scores were used to answer the research questions while t-test statistics was used to test the hypothesis at 0.05 alpha levels. The findings of the study revealed that Guidance counsellors competence is an effective indices that attracts counsellees in public secondary schools in Anambra state. Based on the above finding, it recommended that universities, colleges of Education and other institutions of higher learning where guidance and counselling courses are taught should emphasize the importance of counsellors undergoing training that will make them more effective (competent) in discharging their duties as professional counsellors as well as need for one to have proper training that rooted in psychology which would enabled them to function optimally and effectively as professional counsellors.